WOMEN'S STRUGGLE TO COPE WITH THE MISERY OF LIVING IN A HAREM IN FATIMA MERNISSI'S DREAMS OF TRESPASS, TALES OF A HAREM GIRLHOOD (1994): A FEMINIST APPROACH - LAILI , NAJIKHATUL (2011)
The major problem of this study is to reveal how women's struggle to cope with the misery of living in a harem is reflected in Fatima Mernissi's Dreams of Trespass. The objective of this study is to analyze this memoir based on its structural elements and a feminist approach. In Analyzing Dreams of Trespass, the researcher uses qualitative method. The object of this study is Dreams of Trespass memoir which consists of 242 pages, directed by Fatima Mernissi and distributed by Basic books, New York in 1994. The data sources consist of primary data and secondary data. The primary data source is the Dreams of Trespass memoir itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and feminism, and historical background of Morocco in the twentieth century. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of this study shows the following conclusions. First, from the structural analysis of the memoir shows that each of structural elements forms solid unity. Second, based on Feminist Approach, the conclusion is that there is women's struggle to cope with the misery of living in a harem in Fatima Mernissi's Dreams of Trespass. Moroccan tradition implicitly described that women is as inferior. There is discrimination inside a harem between men and women, such as in position, role, right, and participation.